2016
DOI: 10.1080/14787210.2017.1271711
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of molecular testing in clinical virology

Abstract: The development of quantitative methods for the detection of viral nucleic acids have significantly improved our ability to manage disease progression and to assess the efficacy of antiviral treatment. Moreover, major advances in molecular technologies during the last decade have allowed the identification of new host genetic markers associated with antiviral drug response but have also strongly revolutionized the way we see and perform virus diagnostics in the coming years. Areas covered: In this review, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 144 publications
0
8
0
2
Order By: Relevance
“…25 These molecular assays allow for rapid, highly sensitive and relatively cost-effective identification of viruses in the respiratory tract. 116 Viral culture and serology used to be the main methods of detection in the past, but these techniques were limited due to high cost, labor intensity, and lack of sensitivity. 117 The overall prevalence of viral infections during pulmonary exacerbations in individuals with CF is estimated to be between 13 and 60%.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…25 These molecular assays allow for rapid, highly sensitive and relatively cost-effective identification of viruses in the respiratory tract. 116 Viral culture and serology used to be the main methods of detection in the past, but these techniques were limited due to high cost, labor intensity, and lack of sensitivity. 117 The overall prevalence of viral infections during pulmonary exacerbations in individuals with CF is estimated to be between 13 and 60%.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…These examples represent infections with high disease burden requiring the implementation of automated platforms [1,2]. Consequently, clinical laboratories have seen consolidation of various testing departments into the molecular diagnostic space in a continuous process of technological evolution [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, only faeces obtained with non-invasive procedure is not allowed. Several studies have demonstrated the efficient dPCR platform searching different viruses [20][21][22][23][24][25]. Moreover, rapid, accurate and affordable molecular technology can be predictable with particular emphasis on emerging techniques (next generation sequencing, digital PCR, point of care testing and syndromic diagnosis) to simplify viral diagnosis in the next future [24,25].…”
Section: Resultsmentioning
confidence: 99%